Sixty-six years of the Inhaled Particles symposia—a commentary - John W Cherrie (Annals of Work Exposures and Health, 2026)
Abstract The first Inhaled Particles Symposium was held in 1960 under the leadership of 2 aerosol scientists, Norman Davies and Henry Walton. The study of inhaled particles has evolved over the subsequent decades, encompassing toxicology, epidemiology, aerosol science and occupational hygiene to understand their potential health impacts. Research has progressed from studies of workers in coal mines and those working with asbestos along with other dusts, including talc, radioactive particles, irritant aerosols such as enzymes and other organic dusts, and latterly nanoparticles and nanoplastics. The papers have mostly concerned occupational exposure, although some symposia included sessions on air pollution and cigarette smoke. This commentary briefly summarises some of the key achievements of 14 Inhaled Particles symposia, highlighting advances in particle deposition, clearance, exposure measurement and toxicity assessment. These symposia have fostered multidisciplinary dialogue, although recent meetings have become primarily focused on particle toxicology. It is argued that there is a need to reinvigorate the dialogue between epidemiologists, exposure scientists and toxicologists to develop comprehensive models linking exposure metrics to disease risk. Such integration would enhance risk assessment and inform preventive strategies for diverse inhaled particles. Additionally, preserving the symposia's legacy through an accessible archive would support ongoing research and collaboration in this important scientific field.